Cusco, 1689: economy and society in the southern Andean - Ramos, Gabriela (1982)
We seldom stop to think of the church as an institution whose power and importance are indisputable in social and economic life during the colonial period. The recourse to the documents produced by the church has been rather sporadic in our historiography, and there are still few attempts to use them. The edition of this document, which contains the reports that the priests of the Cuzco diocese wrote between the years 1689-90, under the orders of Bishop Manuel de Mollinedo, opens new tracks for research, and highlights the importance of the use of ecclesiastical sources. .